Analysis of educators’ perceptions regarding career and technical education, academic content, and blended curricula - Handy, Kimberley; Braley, Richard Braley (Journal of Interdisciplinary Studies in Education, 2012)
Career and technical education (CTE) and academic content (AC) curricula are often perceived as conflicting; however, research indicates that a blend of CTE and AC maximizes students’ benefits.  This study identified and categorized educators’ perceptions of CTE and AC curricula in a large school district. Data from the survey and interview responses were transcribed, sorted, coded, and analyzed. The results indicated that educators realized the importance of an individualized teaching approach. Additionally, educators described the importance of blending CTE and AC, as well as obstacles to integration of the curricula. The barriers educators’ perceived to integrating curricula affected the blending of curricula in classrooms. By providing the school district with research-based curricula improvements, students maximize earning, learning, and employment potentials.